2014
DOI: 10.1038/npp.2014.310
|View full text |Cite
|
Sign up to set email alerts
|

Myelin vs Axon Abnormalities in White Matter in Bipolar Disorder

Abstract: White matter (WM) abnormalities are among the most commonly reported neuroimaging findings in bipolar disorder. Nonetheless, the specific nature and pathophysiology of these abnormalities remain unclear. Use of a combination of magnetization transfer ratio (MTR) and diffusion tensor spectroscopy (DTS) permits examination of myelin and axon abnormalities separately. We aimed to examine myelination and axon geometry in euthymic patients with bipolar disorder with psychosis (BDP) by combining these two complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
4
22
1
Order By: Relevance
“…The observed reductions in interhemispheric connectivity in bipolar I disorder patients are consistent with previous reports of reduced integrity of the CC in bipolar disorder [Barysheva et al, ; Emsell et al, ; Lagopoulos et al, ; Leow et al, ; Sarrazin et al, ; Torgerson et al, ; Wang et al, ] and may be reflective of a decrease in the number, density, caliber, and/or myelination of callosal axons, with recent findings pointing more towards myelination than axon abnormalities [Lewandowski et al, ]. Around 200–250 million axons pass through the CC [Nishikimi et al, ; Paul et al, ] to connect primary, secondary, and higher‐order cortices [Aboitiz et al, ].…”
Section: Discussionsupporting
confidence: 89%
“…The observed reductions in interhemispheric connectivity in bipolar I disorder patients are consistent with previous reports of reduced integrity of the CC in bipolar disorder [Barysheva et al, ; Emsell et al, ; Lagopoulos et al, ; Leow et al, ; Sarrazin et al, ; Torgerson et al, ; Wang et al, ] and may be reflective of a decrease in the number, density, caliber, and/or myelination of callosal axons, with recent findings pointing more towards myelination than axon abnormalities [Lewandowski et al, ]. Around 200–250 million axons pass through the CC [Nishikimi et al, ; Paul et al, ] to connect primary, secondary, and higher‐order cortices [Aboitiz et al, ].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, many prior histological studies in BD show fewer overall oligodendrocytes, decreased number of oligodendrocytes per neuron, and reduced expression of myelin‐related genes in the prefrontal cortex in individuals with BD . Together, these studies suggest that myelin‐related pathology may extend into the cerebral cortex in BD.…”
Section: Introductionmentioning
confidence: 75%
“…These findings argue for potentially converging pathophysiologic mechanisms in the two disorders (60). Indeed, the diffusionweighted MRI metric of FA is often interpreted as a proxy of white matter microstructure-rather than a metric of tract volume (35)-and studies have suggested white matter abnormalities in bipolar disorder to be concentrated around a reduction in myelin content rather than abnormalities in axonal geometry or tract volume (61,62). This is in contrast to SCZ, where both myelination deficits and axon abnormalities have been reported (63).…”
Section: Discussionmentioning
confidence: 99%